2014
DOI: 10.1186/bf03352131
|View full text |Cite
|
Sign up to set email alerts
|

Wave observations at the foreshock boundary in the near-Mars space

Abstract: Wave and plasma measurements carried out by the Phobos-2 spacecraft in the Martian environment indicate that a part of solar wind electrons and ions are reflected and accelerated at the Martian bow shock. These particles streaming back into the solar wind lead to the formation of the foreshock region upstream the planetary bow shock. It is shown that the general structure of the foreshock at Mars is similar to that of the foreshock region upstream the Earth's bow shock. However, the electric emissions observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The fifth panel presents wave emissions measured at frequency of 100 Hz. Skalsky et al (1998) indicated that these waves are observed "upstream" of electron plasma oscillations, which have onset near the tangent line, in 30-40% of all circular orbits. No obvious correlation between waves and the magnetic field bending is found.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fifth panel presents wave emissions measured at frequency of 100 Hz. Skalsky et al (1998) indicated that these waves are observed "upstream" of electron plasma oscillations, which have onset near the tangent line, in 30-40% of all circular orbits. No obvious correlation between waves and the magnetic field bending is found.…”
Section: Observationsmentioning
confidence: 99%
“…Picked-up exospheric protons, reflected from the electrostatic barrier at the bow shock, may supply "overreflection" of protons and contribute significantly to the population of backstreaming ions (Dubinin et al, 1994(Dubinin et al, , 1995. Martian ions can generate the wave activity not only in the foreshock region, what is happening in the earth, but also upstream of the tangent line Skalsky et al, 1998). As a consequence, extension of the foreshock study to include the Martian case would be beneficial.…”
Section: Introductionmentioning
confidence: 99%